1988
DOI: 10.1128/mcb.8.12.5549
|View full text |Cite
|
Sign up to set email alerts
|

The human transforming growth factor alpha promoter directs transcription initiation from a single site in the absence of a TATA sequence.

Abstract: Transforming growth factor alpha (TGF-ot) is a transformation-responsive mitogenic polypeptide that is expressed in the brain, epithelial cells, and activated macrophages. We isolated and characterized the TGF-a promoter and localized the 5' end of the TGF-ea transcript to a unique position. Surprisingly, no apparent TATA box was present in the promoter sequence, suggesting that transcription from mammalian genes can initiate at unique and specific positions from promoters lacking this sequence motif.The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 33 publications
2
49
1
Order By: Relevance
“…Deletion to 201 bp of TGFa promoter which removes the adjacent EGF/ TGFa response element, signi®cantly decreases the level of basal CAT activity. Other groups have also reported that deletions which remove this element result in CAT constructs with reduced basal activity (Jakobovits et al, 1988;Raja et al, 1991). Therefore, this EGF/TGFa response element may also be important in maintaining a level of TGFa basal transcription which facilitates the action of more distal (`upstream') elements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deletion to 201 bp of TGFa promoter which removes the adjacent EGF/ TGFa response element, signi®cantly decreases the level of basal CAT activity. Other groups have also reported that deletions which remove this element result in CAT constructs with reduced basal activity (Jakobovits et al, 1988;Raja et al, 1991). Therefore, this EGF/TGFa response element may also be important in maintaining a level of TGFa basal transcription which facilitates the action of more distal (`upstream') elements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this EGF/TGFa response element may also be important in maintaining a level of TGFa basal transcription which facilitates the action of more distal (`upstream') elements. Deletion of the ®rst 370 bp of DNA to generate a construct extending from 71140 to 7370 yields very low CAT activity (only 5% of the total activity) despite the presence of several potential Sp-1 and AP-2 sites within this fragment (Jakobovits et al, 1988). The remaining low-level basal transcription of the p201-CAT construct is probably due to Sp-1 binding at the two potential Sp-1 consensus sequences within this region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second type of TATAless promoter is the GϩC-ich class found in a number of genes. In contrast to TATA-containing promoters, which accurately initiate at a single site, only a few of these GϩC-rich promoters initiate transcription from a single site (29,30), whereas many demonstrate multiple transcription start sites (31)(32)(33). GϩC-rich sequences play a critical role in controlling the expression of various genes, including housekeeping genes and many cellular oncogenes.…”
Section: Discussionmentioning
confidence: 99%